Design science in tourism : foundations of destination management / Daniel R. Fesenmaier, Zheng Xiang, editors. - Fesenmaier, Daniel R.; Xiang, Zheng (Tourism on the verge., 2016)
Exploring the impact of design science and design thinking on tourism planning, this text brings together contributions from leading authorities in the field of tourism research and provides a comprehensive and interconnected panorama of cutting-edge results that influence the current and future design of tourist destinations. The book builds on recent findings in psychology, geography and urban and regional planning, as well as from economics, marketing and communications, and explores the opportunities arising from recent advances in the Internet and related technologies.